ANALYSIS OF THE BIOMECHANICS OF MUSCLE ACTIVITY OF THE LOWER LIMBS USING A CONTACT LED PLATFORM - Voronov A.V.; Shpakov A.V.; Sokolov N.N.; Voronova A.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to evaluate the biomechanical characteristics of the lower limb muscles using a contact LED track. Methods and structure of the study. The study involved 215 high-level athletes (both genders, from masters of sports to masters of sports of international class), as well as young football players aged 16 to 18. The subjects performed three types of vertical jumps, pushing off with both feet: a jump from a half-squat position; a jump with a preliminary squat; a jump with a squat and using a swinging motion of the arms. Results and conclusions. The analysis of the relationship between the height of jumps from a half-squat position and the indices of isokinetic dynamometry revealed that the correlation indices (r) between the height of jumps and the specific moments of force of the quadriceps femoris muscle, measured at an angular velocity of knee extension of 60 degrees/sec, vary from 0.5 to 0.9, depending on the specifics of the sport. The use of elastic properties of muscles by means of a preliminary squat and a reactive impulse from arm swing movements provides an increase in the height of jumps by an average of 30.4±8.6% compared to jumps performed from a half-squat position. The highest values ​​of the coordination coefficient (CC) are noted in athletes involved in cycling (CC> 15%). In football players and cyclists, the coefficient of elasticity (CE) exceeds the similar indicator in speed skaters and skiers (among men) by 2-3 times. In female athletes, the potential for elastic energy accumulation does not exceed KE<7%.